The Effect of Loading and Unloading Delays and Truck Fleet Readiness on Operating Performance - Yulianti Keke; Natalia Ayu Hapsari Keke; Anandita Shafa; Siska Amonalisa Silalahi; Veronica Veronica; Yolla Ayutia; Devi Ratnasari (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Operational performance is a critical factor in logistics management, directly affecting service quality, customer satisfaction, and overall company efficiency. Delays in unloading processes and the readiness of the truck fleet are common challenges that can hinder smooth operations. This study aims to examine how unloading delays and truck fleet readiness influence operational performance. A quantitative research method was employed, with data collected through questionnaires distributed to 30 operational staff members. Data were analyzed using SPSS version 26, including validity and reliability tests and multiple linear regression analysis. The results indicate that both unloading delays and truck fleet readiness have a significant impact on operational performance, both individually and collectively. The coefficient of determination shows that approximately 55.3% of operational performance variation is explained by these factors, while the remaining portion is influenced by other variables outside the scope of this study. These findings highlight the importance of optimizing unloading efficiency and ensuring fleet readiness to enhance overall operational performance.